Pengaruh Kualitas Produk dan Citra Merek Handphone Samsung Terhadap Keputusan Pembelian Konsumen di Kota Palembang - Rawong, Nicholas; Valencio, Verrell; Bestra, Fabio (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
The core of this research is to determine the impact of the product quality and image of the Samsung mobile phone brand on consumer purchasing decisions in the city of Palembang. The study aims to find out whether the quality of the product and brand image of samsung affects consumer mobile phone purchasing decisions, as well as providing advice and input to samsung brand. The method used in this research is the quantitative method of the survey method, by spreading the questionnaire. The questionnaire contains questions about the quality and image of the Samsung phone brand according to the questionnaire fillers. The target of this questionnaire is those smartphone users. The benefits of this research are expected to have a positive impact on Samsung products, which is to correct the shortcomings that Samsung products have. Using the method of survey/fill questionnaire and statistical analysis, it is expected that the results of this research can give a clear form about the influence of product quality and brand image of samsung on smartphone purchase decisions in the city of Palembang.